516. MICRONUTRIENT DEFICIENCIES AFTER GASTROESOPHAGEAL CANCER SURGERY. (24th September 2022) - Blonk, Lotte; Gooszen, JAH; Fakkert, R; Eshuis, WJ; Rietveld, S; Straatman, J; Gisbertz, SS; van Berge Henegouwen, MI
Abstract: Due to inadequate dietary intake and altered digestion and absorption of nutrients, patients after gastroesophageal cancer surgery are at high risk of becoming malnourished and to develop deficiencies in micronutrients. The goal of this study was to determine the prevalence of specific micronutrient deficiencies during follow-up. This single center prospective study included patients who underwent resection for esophageal or gastric cancer and were still alive at follow-up between January 2016 and December 2017. All patients in this study were guided by a dietician and dietary supplements or tube feeding was prescribed in case of inadequate dietary intake. Blood samples were examined for possible deficiencies in calcium, ferritin, folic acid, vitamin A, vitamin B1, vitamin B6, vitamin B12, vitamin D, vitamin E, and zinc. Primary endpoint of this study was the prevalence of specific micronutrient deficiencies. 149 patients after esophagectomy and 32 after gastrectomy were included. After esophagectomy early postoperative deficiencies (<12 months after surgery, measurements performed in 68 patients) and late postoperative deficiencies (≥12 months after surgery, measurements performed in 81 patients) were seen in vitamin D (35.8% and 25.0%) and zinc (22.6% and 16.7%). After gastrectomy vitamin D (47.4%), zinc (29.4%), vitamin B1 (15.8%) and ferritin (15.8%) were found to be deficient <12 months after surgery (measurements performed in 19 patients). Vitamin D (46.2%), zinc (16.7%), vitamin A (15.4%), and ferritin (15.4%) were deficient in the late postoperative period (measurements performed in 13 patients). This single center prospective study showed that, despite active nutritional guidance, deficiencies in vitamin D, vitamin B1, vitamin A, zinc, and ferritin are prevalent following gastroesophageal resection for cancer and should therefore be routinely checked during follow-up and prophylactic supplementation to prevent deficiencies is indicated.